2011
DOI: 10.1128/iai.05124-11
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Role for Hsp82 in Histoplasma Virulence through a Quantitative Screen for Macrophage Lethality

Abstract: The application of forward genetics can reveal new factors required for the virulence of intracellular pathogens. To facilitate such virulence screens, we developed macrophage cell lines with which the number of intact host cells following infection with intracellular pathogens can be rapidly and easily ascertained through the expression of a constitutive lacZ transgene. Using known virulence mutants of Francisella novicida and Histoplasma capsulatum, we confirmed the applicability of these host cells for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…To determine the role of Cfp4 in macrophage killing, we utilized the previously described P338D1-lacZ macrophage killing assay in which macrophage-expressed LacZ is used as an indicator of surviving macrophages (17). Macrophages were maintained in Ham's F-12 with 10% heat-inactivated fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the role of Cfp4 in macrophage killing, we utilized the previously described P338D1-lacZ macrophage killing assay in which macrophage-expressed LacZ is used as an indicator of surviving macrophages (17). Macrophages were maintained in Ham's F-12 with 10% heat-inactivated fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
“…Within phagocytes, Histoplasma yeasts grow and replicate, ultimately leading to lysis of the phagocyte and spread of the infection. A few factors facilitating the intramacrophage lifestyle of Histoplasma are beginning to be defined (11) and include Cbp1, a secreted factor of unknown function (12), production of siderophores and iron reductase systems that enable iron acquisition within the phagosome (13)(14)(15), de novo synthesis of essential vitamin cofactors (16), and thermotolerance (17).…”
mentioning
confidence: 99%
“…Flanking sequences were identified by PCR and sequencing. The authors identified a new virulence gene in Histoplasma, a homolog of Hsp82 (Edwards et al, 2011). Marion et al (2006) performed a more comprehensive analysis of insertional mutagenesis in Histoplasma capsulatum using Agrobacterium-mediated transformation.…”
Section: Agrobacterium T-dnamentioning
confidence: 99%
“…Researchers have developed protocols that have improved the efficiency of transformation using T-DNA in C. neoformans (Idnurm et al, 2004), Histoplasma and Blastomyces (Brandhorst et al, 2002;Edwards et al, 2011;Gauthier et al, 2010;Laskowski and Smulian, 2010;Marion et al, 2006;Smulian et al, 2007;. In addition, T-DNA mutagenesis protocols have been developed for Coccidioides (Abuodeh et al, 2000), Trichoderma spp.…”
Section: Agrobacterium T-dnamentioning
confidence: 99%
See 1 more Smart Citation